Aplikasi Monitoring Berat Badan Ibu Hamil - Nana Windiarto; Nia Saurina; Noven Indra Prasetya (Informatics Engineering Department-UWKS, 2016)
Pregnancy is a time of commencement of conception to birth the fetus. In fact important for pregnant women to maintain a weight gain due to avoid the risk of LBW (low birth weight). To calculate the ideal pattern of weight gain for pregnant women need the calculation of BMI (body mass index) in order to determine the threshold goal and BMI categories. Therefore this penelitiaan bertujuaan to make mobile android application that functions to help expectant mothers during pregnancy in order to continue to maintain ideal body weight, thereby reducing LBW. The data obtained in the study of literature sourced books and interviews. This application design using Unified Modeling Language (UML) to manufacture android based application programming blog. In this study generated application monitoring weight pregnant women. The output of this application the user can determine the ideal weight should include weight, weight gain and suggestions should the addition or subtraction of weight